Detailed Hearing and Vestibular Profiles in the Patients with COCH Mutations. (May 2015) - Tsukada, Keita; Ichinose, Aya; Miyagawa, Maiko; Mori, Kentaro; Hattori, Mitsuru; Nishio, Shin-ya; Naito, Yasushi; Kitajiri, Shin-ichiro; Usami, Shin-ichi
Objectives: To evaluate the clinical features of Japanese DFNA9 families with mutations of the COCH gene. Methods: Mutation screening was performed using targeted next-generation sequencing (NGS) for 63 previously reported deafness genes. The progression of hearing loss and vestibular dysfunction were evaluated by pure-tone audiometry, caloric testing, cVEMP, and computed dynamic posturography. Results: We detected 1 reported mutation of p.G88E and 2 novel mutations of p.I372T and p.C542R. The patients with the novel mutations of p.I372T and p.C542R within the vWFA2 domain showed early onset progressive hearing loss, and the patients with the p.G88E mutation showed late onset hearing loss and acute hearing deterioration over a short period. Vestibular symptoms were reported in the patients with p.G88E and p.C542R. Vestibular testing was performed for the family with the p.G88E mutation. Severe vestibular dysfunction was observed in the proband, and the proband's son showed unilateral semicircular canal dysfunction with mild hearing loss. Conclusions: Targeted exon resequencing of selected genes using NGS successfully identified mutations in the relatively rare deafness gene, COCH, in the Japanese population. The phenotype is compatible with that described in previous reports. Additional supporting evidence concerning progressive hearing loss and deterioration of vestibular function was obtained from our study.